Inhibitory interactions between two inward rectifier K+ channel subunits mediated by the transmembrane domains. - Tucker, S; Bond, C; Herson, P; Pessia, M; Adelman, J (1996)
Inwardly rectifying K+ channel subunits may form homomeric or heteromeric channels with distinct functional properties. Hyperpolarizing commands delivered to Xenopus oocytes expressing homomeric Kir 4.1 channels evoke inwardly rectifying K+ currents which activate rapidly and undergo a pronounced decay at more hyperpolarized potentials. In addition, Kir 4.1 subunits form heteromeric channels when coexpressed with several other inward rectifier subunits. However, coexpression of Kir 4.1 with Kir 3.4 causes an inhibition of the Kir 4.1 current. We have investigated this inhibitory effect and show that it is mediated by interactions between the predicted transmembrane domains of the two subunit classes. Other subunits within the Kir 3.0 family also exhibit this inhibitory effect which can be used to define subgroups of the inward rectifier family. Further, the mechanism of inhibition is likely due to the formation of an "inviable complex" which becomes degraded, rather than by formation of stable nonconductive heteromeric channels. These results provide insight into the assembly and regulation of inwardly rectifying K+ channels and the domains which define their interactions.